Routledge handbook of physical education pedagogies - Ennis, Catherine D.; Armour, M. Kathleen; Ang Chen; Garn, Alex C.; Mauerberg-DeCastro, Elaine; Penney, Dawn; Silverman, Stephen J.; Solmon, Melinda A.; Tinning, Richard (London New York Routledge, 2019)
The first fully comprehensive review of theory, research, and practice in physical education to be published in over a decade, this handbook represents an essential, evidence-based guide for all students, researchers, and practitioners working in PE. Showcasing the latest research and theoretical work, it offers important insights into effective curriculum management, student learning, teaching, and teacher development across a variety of learning environments. This handbook not only examines the methods, influences, and contexts of physical education in schools, but also discusses the implications for professional practice. It includes both the traditional and the transformative, spanning physical education pedagogies from the local to the international. It also explores key questions and analysis techniques used in PE research, illuminating the links between theory and practice. Its nine parts cover a wide range of topics including: curriculum theory, development, policy, and reform; transformative pedagogies and adapted physical activity; educating teachers and analyzing teaching; the role of student and teacher recognition; achievement motivation. Offering an unprecedented wealth of material, the Routledge handbook of physical education pedagogies is an essential reference for any undergraduate or postgraduate degree program in physical education or sports coaching, and any teacher training course with a physical education element
Part I. Designing and conducting physical education research -- Part II. Curriculum theory and development -- Part III. Curriculum policy and reform -- Part IV. Adapted physical activity -- Part V. Transformative pedagogies in physical education -- Part VI. Analyzing teaching -- Part VII. Educating teachers effectively from PETE to CPD -- Part VIII. The role of student and teacher cognition in student learning
Routledge international handbooks
Keywords: Physical education and training -- Handbooks, manual, etc; Physical education and training -- Study and teaching